FROM TEACHER TO FACILITATOR: THE ROLE OF EDUCATORS IN SUPPORTING HEUTAGOGICAL PRACTICES IN HIGHER EDUCATION - Misbahul Khairani; Nurul Huda; Faisal Razak; Dyah Retno Wulan (Yayasan Adra Karima Hubbi, 2025)
The rapid evolution of educational paradigms in the 21st century has underscored the necessity for a shift from traditional teacher-centered instruction to more learner-driven approaches, such as heutagogy. Heutagogy emphasizes self-determined learning, where learners are empowered to take control of their educational journey. This study aims to explore the evolving role of educators in higher education as they transition from knowledge transmitters to facilitators of autonomous learning within heutagogical frameworks. Employing a qualitative approach, data were collected through in-depth interviews and focus group discussions involving 15 university lecturers across various disciplines. Thematic analysis revealed that educators play a pivotal role in designing flexible learning environments, fostering learner agency, and integrating digital tools to support independent learning pathways. Challenges identified include institutional constraints, limited professional development, and resistance to pedagogical change. However, the findings indicate that with proper training and institutional support, educators can effectively adapt their roles to facilitate heutagogical practices. The study concludes that the transformation of educators into facilitators is crucial for nurturing self-determined learners capable of navigating complex and dynamic knowledge landscapes.